Epidemiological profile of pregnant women with HIV in a maternity hospital in São Paulo – SP, Brazil - Nascimento, Leandra; Chiattone, Maria Fernanda; Archondo, Marcia Eugenia; Yakabe, Clarice (Brazilian Journal of Global Health, 2022)
OBJETIVO: A síndrome de imunodeficiência adquirida (AIDS) é uma doença pandêmica que representa um desafio para a saúde pública. Esse trabalho objetivou traçar o perfil epidemiológico de gestantes portadoras do vírus HIV atendidas em um Hospital Maternidade de alta complexidade na zona norte da cidade de São Paulo – SP, Brasil. MÉTODOS: Os dados foram obtidos por meio de busca ativa nos prontuários de pacientes internadas e nas fichas de notificação de casos de HIV, do Serviço de Controle de Infecção Hospitalar (SCIH) no período de 2019 a 2021. RESULTADOS: Os resultados mostraram que a maior parte das gestantes HIV positivas atendidas na maternidade no período do estudo são jovens entre 21 e 31 anos, 40% eram solteiras e 39% afirmaram estar em união consensual, 60% completaram apenas o ensino fundamental, a maioria está desempregada, 58,5% se autodeclararam pardas e 35% foram diagnosticadas na gestação. Do total 89,4% aderiram ao tratamento e a principal via de parto foi parto vaginal o que mostra aderência à profilaxia TARV. Quase a totalidade dos neonatos receberam profilaxia antirretroviral. CONCLUSÃO: O diagnóstico precoce e o tratamento são fundamentais para o nascimento saudável do bebê. Os dados obtidos nesse estudo permitem conhecer melhor o perfil das gestantes HIV positivo atendidas na maternidade e assim desenvolver programas de assistência no período de gestação e pós-parto. DESCRITORES: HIV, Gestantes, Perfil epidemiológico. ABSTRACT OBJECTIVE: Acquired immunodeficiency syndrome (AIDS) is a pandemic disease that poses a public health challenge. This study aimed to trace the epidemiological profile of pregnant women with the HIV virus treated at a high complexity Maternity Hospital in the north of the city of São Paulo – SP, Brazil. METHODS: Data were obtained through an active search in the medical records of hospitalized patients and in the HIV case notification forms, from the Hospital Infection Control Service (SCIH) in the period from 2019 to 2021. RESULTS: The results showed that the majority of the HIV positive pregnant women seen at the maternity hospital during the study period were young, between 21 and 31 years old, 40% were single and 39% said they were in a consensual union, 60% completed only elementary school, most were unemployed, 58.5% declared themselves to be brown, and 35% were diagnosed with HIV during pregnancy. Of the total, 89.4% adhered to treatment and the main route of delivery was vaginal delivery, which demonstrates the adherence to antiretroviral therapy (ART) prophylaxis. Almost all neonates received antiretroviral prophylaxis. CONCLUSION: Early diagnosis and treatment are essential for the healthy birth of the baby. The data obtained in this study allow us to better understand the profile of HIV-positive pregnant women treated at the maternity ward, and thus to develop assistance programs in the gestation and postpartum period. DESCRIPTORS: HIV, Pregnant women, Epidemiological profile.